Subvolcanic petrology of the Pico dos Três Estados region (SE Brazil): Implications for Alkaline Magmatic Evolution - Graciano Carlos de Freitas; Artur Corval; Júlio Cesar Lopes da Silva; Helena Saraiva Koenow Pinheiro; Sérgio de Castro Valente (Brazilian Journal of Geology)
Abstract This paper presents a geological study of the subvolcanic bodies present in the Pico dos Três Estados (São Paulo (SP), Rio de Janeiro (RJ), and Minas Gerais (MG)) and its surroundings at the Passa Quatro Alkaline Complex. In this study, we used field-collected data, petrography, and geochemical analysis data. From a more detailed fieldwork, we verified that the region that appeared to present only two lithologies in previous works presented a faciological complex with at least six distinct facies, with emphasis on the phonolitic body that forms the Pico dos Três Estados (2,665 m high). Still regarding fieldwork, we found that there are signs of magma mingling processes in the area. Modeling indicates that 10% of fractional crystallization was able to derive the phonolitic rocks from a trachytic liquid based on the following elements: Y, Nb, Yb, Ce, Sm, Eu, La, Nd, Hf, and Pr. The modal batch partial melting shows the possible mantle sources for the magmatism in this area. This data pointed out the involvement of an enriched mantle source in the La/Yb ratio by at least 16 times more than an Oceanic Island Basalt (OIB)-type mantle.